Review On Secure and Distributed Reprogramming Protocol (International Journal of Engineering and Computer Science, 2017)
Wireless reprogramming is very important in sensor networks. Reprogramming is defined as the process of loading a new code image or relevant commands to sensor nodes. For security reasons every code update must be authenticated to prevent an attacker from installing malicious scripts in the network. A number of protocols have been defined for reprogramming the wireless sensor networks. SDRP is the first distributed reprogramming protocol in which multiple authorized network users can simultaneously and directly reprogram sensor nodes without involving the base station. The protocol uses identity-based cryptography to secure the reprogramming and to reduce the communication and storage requirements of each node. Preserving data privacy is a challenging problem in wireless sensor networks. On comparison, Elliptic Curve Integrated Encryption Scheme (ECIES) provides great solution for security and authorization in the sensor network.